PERIZINAN PERTAMBANGAN BATUAN DALAM MEWUJUDKAN TATA KELOLA YANG BERWAWASAN LINGKUNGAN - Saliha, Retnadumillah (Katalogis, 2017)
The research was to identify the roles of provincial Government of Central Sulawesi in the line with authority to grant rock mining permit pursuant to Law Number 4 year 2009 about Mineral and Coal Mining and Law Number 23 Year 2014 about Provincial/City/Regency Government, in the line with environmental controlÂ to realize sustainable eco-friendly mining governance. It was a normative or legal research adoptingÂ statute approach by reviewing all laws and regulations related with rock mining permit and environmental protections and conceptual approach by observing various problems arising and related with rock mining permits synchronized with environmental protection measures. The results of the research showed that the Provincial Government of Central Sulawesi is fully authorized and the control to secure eco-friendly mining govenance was not yet maximal due to overlapping and incomplete mining laws and regulations, limited human resources to cover such a wide geographical mining area and lack of coordination of control among the related authorities and institution concerning with mining controlÂ and environment. The recommended step is to revise the Law Number 4 year 2009 about Mineral and Coal Mining and Law Number 23 Year 2014 about Provincial/City/Regency Government to secure a sustainable and eco-friendly development.